“Green for Whom?” Examining the impact of Green Transitions on Park Accessibility and Green Gentrification in Malmö’s Western Harbour - Todino,Astrid I (2025)
This thesis explores the correlation between green transitions and green gentrification, using the case study of the Western Harbour in Malmö, Skåne. More specifically, through the lens of the Right to the City and Environmental Justice, this thesis looks into the accessibility to green spaces in the Western Harbour for different socio-economic groups. Expert interviews, qualitative surveys with residents and ethnographic observations were conducted, revealing that the green urban renewal of the Western Harbour is an example of green gentrification affecting negatively low income resident’s access to the green spaces in the area. Furthermore, results show that the greening of the Western Harbour challenge the theoretical perspectives of the Right to the City and Environmental Justice
Keywords: Green gentrification; accessibility; green spaces; social inequalities; Right to the City